Contrast Analysis of Indonesian and Malay-Jawi Vocabulary: A Linguistic Study at Santwit Songkhla Technological College - Eli Marlina Harahap; Lili Herawati Parapat; Nur Afifah; Nurmaini Ginting; Rosinah; Elfa Fadhilah Lubis (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to analyze the similarities and differences in vocabulary between Indonesian and Jawi Malay through a contrastive analysis approach in the educational context at Santiwit Songkhla Technological College, Southern Thailand. Although both languages ​​have a close genealogical relationship as cognate languages ​​in the Austronesian family, contrastive studies that specifically highlight the lexical variation of Jawi Malay in the educational context in Southern Thailand are still limited. This study uses a qualitative approach with a comparative descriptive method. Data in the form of 50 basic Indonesian vocabulary words matched with their representation of Jawi Malay in Jawi script, were obtained through written instruments from 25 bilingual Thai Malay respondents. The results show that most vocabulary words show lexical variation with equivalent core meaning, while Jawi script functions as a graphemic representation system and not as a structural differentiating factor of language. Variations found include form retention, minor phonological changes, total lexical substitution, and pronominal variation. This finding confirms that lexical variation in cognate languages ​​is a form of natural divergence influenced by the social context and language habits of its speakers, and has important implications for learning cognate languages.